Rethinking Secularism. - Calhoun, Craig (Oxford University Press USA- OSO, 2011)
This collection of essays examines how "the secular" is constituted and understood, and how new understandings of secularism and religion shape analytic perspectives in the social sciences, politics, and international affairs.